Drinking patterns vary by gender, age and country‐level income: Cross‐country analysis of the International Alcohol Control Study. (13th June 2018) - Chaiyasong, Surasak; Huckle, Taisia; Mackintosh, Anne‐Marie; Meier, Petra; Parry, Charles D. H.; Callinan, Sarah; Viet Cuong, Pham; Kazantseva, Elena; Gray‐Phillip, Gaile; Parker, Karl; Casswell, Sally
Abstract: Introduction and Aims: Gender and age patterns of drinking are important in guiding country responses to harmful use of alcohol. This study undertook cross‐country analysis of drinking across gender, age groups in some high‐and middle‐income countries. Design and Methods: Surveys of drinkers were conducted in Australia, England, Scotland, New Zealand, St Kitts and Nevis (high‐income), Thailand, South Africa, Mongolia and Vietnam (middle‐income) as part of the International Alcohol Control Study. Drinking pattern measures were high‐frequency, heavier‐typical quantity and higher‐risk drinking. Differences in the drinking patterns across age and gender groups were calculated. Logistic regression models were applied including a measure of country‐level income. Results: Percentages of high‐frequency, heavier‐typical quantity and higher‐risk drinking were greater among men than in women in all countries. Older age was associated with drinking more frequently but smaller typical quantities especially in high‐income countries. Middle‐income countries overall showed less frequent but heavier typical quantities; however, the lower frequencies meant the percentages of higher risk drinkers were lower overall compared with high‐income countries (with the exception of South Africa). Discussion and Conclusions: High‐frequency drinking was greater in high‐income countries, particularly in older age groups. Middle‐income countries overall showed less frequent drinking but heavier typical quantities. As alcohol use becomes more normalised as a result of the expansion of commercial alcohol it is likely frequency of drinking will increase with a likelihood of greater numbers drinking at higher risk levels.